Pelatihan Audit Internal Dalam Mendukung Penerapan Iso 9001 : 2015 Pada Universal Trading - Surabaya - Benih Hartanti (COMVICE: Journal Of Community Service, 2021)
Abstract Internal audit as a form of implementation of a management audit has a general purpose to provide recommendations for improvements to company management programs or activities. This community service activity (PKM) is carried out at Universal Trading Surabaya, which is a trading company with commodity products with very complex business processes. The purpose of carrying out an internal audit is to maintain service and product quality as a mandatory clause in ISO 9001: 2015 certification. The target of this activity is that company employees are able to carry out a series of ISO audit surveillance activities which have been carried out every six months since 2017. PKM activities are carried out intensively in the form of intensive training for approximately a month, namely in January 2020. From the results It is hoped that the partners will be able to carry out the internal audit process on a regular basis as a concrete form of the company's commitment to maintaining work quality from a quality management system perspective.